2017
DOI: 10.14336/ad.2016.0819
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Concentration is Associated with Incident Frailty in Older Adults

Abstract: Obesity has been associated with higher risk of frailty in older adults, but the pathophysiological mechanisms are unclear. No previous study has examined the association between leptin, an adipokine, and the risk of frailty in older adults, and whether this association could be explained by insulin resistance or chronic inflammation. Data were taken from 1,573 individuals without diabetes mellitus, aged ≥60 years, from the Seniors-ENRICA cohort. In 2008-2010, leptin, the homeostasis model assessment of insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 38 publications
0
18
0
5
Order By: Relevance
“…Leptin receptors gene expression in cell cultures may depend on leptin concentration. It was shown that the addition of exogenous leptin to the cell culture reduced the expression of its receptors, while the decrease in the concentration of circulating leptin during prolonged fasting was accompanied by an increase in receptor mRNA levels [36,37]. In addition, it is currently hypothesized that increased concentrations of the leptin R inhibit leptin effects, while reduced concentrations of the leptin receptor re ect low membrane expression of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin receptors gene expression in cell cultures may depend on leptin concentration. It was shown that the addition of exogenous leptin to the cell culture reduced the expression of its receptors, while the decrease in the concentration of circulating leptin during prolonged fasting was accompanied by an increase in receptor mRNA levels [36,37]. In addition, it is currently hypothesized that increased concentrations of the leptin R inhibit leptin effects, while reduced concentrations of the leptin receptor re ect low membrane expression of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin's effect to augment renal sodium reabsorption occurs by a direct tubular action, by enhancing the synthesis of aldosterone and by mediating the high renal sympathetic nerve traffic that is seen in obesity . High levels of leptin are strongly associated with co‐morbidities, and leptin participates in the inflammatory response in rheumatoid arthritis, psoriasis and Crohn's disease . Increases in leptin are associated with ventricular fibrosis and diastolic filling abnormalities, and contribute to the atrial fibrosis that leads to arrhythmias .…”
Section: Evolution Of Obesity‐related Heart Failure With Preserved Ejmentioning
confidence: 99%
“…Экспрессия рецепторов лептина в клеточных культурах может быть связана с концентрацией лептина. Добавление экзогенного лептина к культуре клеток снижало экспрессию его рецепторов [44], тогда как снижение концентрации циркулирующего лептина при длительном голодании, напротив, сопровождается ростом уровня мРНК OB-R [45].…”
Section: диагностика лептинорезистентностиunclassified